Confirmatory Factor Modeling on Emerging Consumer Purchase Behaviour of Passenger Cars - Menon, Balakrishnan; V. P., Jagathy Raj (Indian Journal of Marketing, 2013)
With globalization and liberalization, many world leaders in automobile manufacturing such as Ford, General Motors, Honda, Toyota, Suzuki, Hyundai, Renault, Mitsubishi, Benz, BMW, Volkswagen and Nissan set up their manufacturing units in India in joint venture with their Indian counterpart companies, by making use of the Foreign Direct Investment policy of the Government of India. With a multiplicity of choices available to the Indian car buyers, it drastically changed the car purchase scenario in India, and particularly in the State of Kerala. This transformed the automobile scene from a sellers’ market to a buyers’ market. The main purpose of this paper was to develop a model with major variables that influenced the consumer purchase behaviour of passenger car owners in the State of Kerala. The results of the research contribute to the practical knowledge base of the automobile industry, specifically to the passenger car segment. It would also lend a great contributory value addition to the manufacturers and dealers for customizing their marketing plans in the State.